Assessment of Physical Activity and Energy Expenditure: An Overview of Objective Measures - Hills, Andrew P.; Mokhtar, Najat; Byrne, Nuala M. (Frontiers in Nutrition, 2014)
The ability to assess energy expenditure and estimate physical activity in free-living individuals is extremely important in the global context of non-communicable diseases including malnutrition, overnutrition (obesity) and diabetes. It is also important to appreciate that physical activity and energy expenditure are different constructs with physical activity defined as any bodily movement that results in energy expenditure and accordingly, energy is expended as a result of physical activity. However, total energy expenditure, best assessed using the criterion doubly labelled water technique, includes components in addition to physical activity energy expenditure, namely resting energy expenditure and the thermic effect of food. Given the large number of assessment techniques currently used to estimate physical activity in humans, it is imperative to understand the relative merits of each. The goal of this review is to provide information on the utility and limitations of a range of objective measures of physical activity and their relationship with energy expenditure. The measures discussed include those based on energy expenditure or oxygen uptake including doubly labelled water, activity energy expenditure, physical activity level, and metabolic equivalent; those based on heart rate monitoring and motion sensors; and because of their widespread use, selected subjective measures.